Desenvolvimento do aço inoxidável supermartensítico resistente ao desgaste por conformação por spray para aplicação em "risers" - Zepon, Guilherme (2013)
The oil exploitation and production in the pre-salt layers in safe, efficient and economically viable way depend on the development of materials that bear the severe conditions found in their applications during their whole life cycle. The pipes used in the oil exploitation and production such as drilling risers are subjected to severe work conditions. The stainless steel grades, such as the supermartensitic, duplex and superduplex, present the corrosion resistance and mechanical properties suit to the application in pipes used the oil exploitation, however, these materials present low wear resistance. Recent studies performed in the Materials Engineering Department at the Federal University of São Carlos (DEMa-UFSCar) have shown that the boron addition in stainless steel grades composition promotes borides formation, which increases the wear resistance of these materials. In this context, this protect aims the study of the wear resistance of spray-formed supermartensitic stainless steel with small additions of boron in its composition. This process allows the attainment of deposits with refined and homogeneous microstructure and with uniformly distributed precipitates directly from the liquid metal. The materials produced were characterized trough the techniques of X-ray diffraction (XRD), Optical microscopy (OM), scanning electron microscopy (SEM) and chemical microanalysis by energy dispersive spectroscopy (EDS). The materials wear resistance was evaluated trough the dry sand against rubber wheel test (ASTM G65-04) and trough a developed test that simulate one of the wear conditions that can occur in oil drilling risers. The results showed that the boron addition in supermartensitic stainless and the boride formation act differently in the materials wear resistance depending on the type of wear mechanism observed.